Islamic Religious Views in Indonesia on Employment Social Security and the Strategic Role of Ulama - Arief Dahyan Supriadi; Tarimantan Sanberto Saragih; A.M. Wibowo; Fadly Eka Pradana; Rendra HF Hutabarat (Green Publisher Indonesia, 2024)
This research discusses Islamic religious views in Indonesia related to employment social security and the strategic role of ulama in its spread. In the context of BPJS Ketenagakerjaan, which aims to protect workers from social and economic risks, ulama play a role as a leader who guides the community in understanding the concept of social security according to Islamic teachings. This study shows that despite skepticism about these programs, a religious organization-based approach can increase community participation. Using a descriptive qualitative method, this study analyzes the views of various religious organizations, including NU, Muhammadiyah, and MUI, towards BPJS Ketenagakerjaan. The results show the importance of ulama fatwas and the integration of Islamic values in social security programs to increase public awareness and participation.